Modified flower-like nickel oxide on carbon paste electrode (CPE) for analysis cholesterol based on non-enzymatic sensor. Issue 1 (February 2020) - Suropati, R T L; Wibowo, R; Nurani, D A; Krisnandi, Y K
Abstract: The increasing circulation of unhealthy foods in various places threatens the community of malnutrition. One of which is the intake of cholesterol nutrition. When the normal limit is exceeded, it can trigger the spread of various diseases such as coronary heart disease. To anticipate the outbreak of the disease, a practical, stable, simple, and relatively inexpensive, non-enzymatic sensor device for monitoring blood cholesterol levels in some food samples such as milk and meat was developed. In this research, nickel modified catalyst on carbon paste electrodes, NiO/CPE by hydrothermal method and Ni/CPE by electrochemical method were developed. A flower-like morphology for NiO was obtained from hydrothermal method and rock-like morphology was obtained from nickel deposit. Results showed that Ni/CPE worked optimally at pH 14 with sensitivity of 0.8148 μA μM −1 cm −2 and limit of detection (LoD) of 0.1645 μM, while NiO/CPE worked optimally at pH 12 with a sensitivity of 0.1238 μA μM −1 cm −2 and LoD of 0.7804 μM. Cholesterol level measurement from the packaged milk sample showed differences of 20.42 % and 47.18 % from the nutrition table information for Ni/CPE and NiO/CPE, respectively.